2014
DOI: 10.1371/journal.pone.0104457
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Associated with Success Rates of Australian Stock Herding Dogs

Abstract: This study investigated the current management practices associated with stock herding dogs on Australian farms. A parallel goal was to determine whether these practices and the characteristics of the dog handlers were associated with success rates. Success rate refers to the proportion of dogs acquired by the farmer that were retained as working dogs. Data on a total of 4,027 dogs were obtained through The Farm Dog Survey which gathered information from 812 herding dog owners around Australia. Using logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Enriched environments in scent detection dogs could therefore potentially reduce the number of errors during scent identification. In dogs, there are clear links between poor welfare and performance, as frustrated, apathetic, or fearful dogs have more difficulty in learning and decreased attention (Arnott et al, 2014;Haverbeke, Laporte, Depiereux, Giffroy, & Diederich, 2008;Rooney, Gaines, & Hiby, 2009). These findings were collected with working dogs from several sources-stock-herding dogs and military dogs, indicating a general effect in dogs, which can be expected to apply to scent detection dogs too.…”
Section: Performance-limiting Factorsmentioning
confidence: 92%
See 1 more Smart Citation
“…Enriched environments in scent detection dogs could therefore potentially reduce the number of errors during scent identification. In dogs, there are clear links between poor welfare and performance, as frustrated, apathetic, or fearful dogs have more difficulty in learning and decreased attention (Arnott et al, 2014;Haverbeke, Laporte, Depiereux, Giffroy, & Diederich, 2008;Rooney, Gaines, & Hiby, 2009). These findings were collected with working dogs from several sources-stock-herding dogs and military dogs, indicating a general effect in dogs, which can be expected to apply to scent detection dogs too.…”
Section: Performance-limiting Factorsmentioning
confidence: 92%
“…It is therefore essential that handlers and trainers are fully aware of how their own behavior and actions may impact on their dog's future performance, beyond the provision of any intended reinforcement. This area requires much more research, although it is clear from several survey-based studies with pet dogs (Eskeland, Tillung, & Bakken, 2007;Hiby, Rooney, & Bradshaw, 2004), working dogs (Arnott, Early, Wade, & McGreevy, 2014), and military dogs (Haverbeke et al, 2010) that there is a relationship between training method and undesired behavior; dogs subjected to more punishment-based training methods also engage in more unwanted behavior. However, the correlational nature of these studies means that the causal direction of this relationship (if any) cannot…”
Section: Training Regimesmentioning
confidence: 99%
“…When looking into efficacy, no study shows a superior efficacy when comparing an e-collar to positive reinforcement training. Some survey-based studies conclude a superior efficacy of positive reinforcement training as perceived by owners (Hiby et al, 2004;Blackwell et al, 2012) or results below average for e-collar training when compared with any other training method (Arnott et al, 2014). One experimental study found no difference in efficacy but a decrease in welfare when using e-collars (Cooper et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…STE allows determining the strain (ST) and strain rate (STR) of LV myocardial deformation in orthogonal planes in the radial, longitudinal, and circumferential directions, and in tangential planes, caused by the sliding of muscle layers from the endocardium to the epicardium [18]. Although these variables have been validated in dogs [9,11,50] and have been used to evaluate heart diseases [15,38,43], the behavior of these variables relative to adaptations promoted by physical activities like snow sled pulling [40] agility competitions [34], running competitions [27] and herding [2,5,22,41,51] remains unknown.…”
Section: Introductionmentioning
confidence: 99%